2021
DOI: 10.3390/pharmaceutics13111916
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin as Functional Carrier in Development of Mucoadhesive Tablets Containing Polygoni cuspidati Extract with Potential for Dental Applications

Abstract: Polygoni cuspidati root is a resveratrol-rich source with anti-inflammatory, angiogenic and neuroprotective effects. The raw material was standardized for the content of resveratrol, for which there is a special justification for administration within the oral mucosa. To improve the solubility of resveratrol and to assure its high content in plant material, an ultrasound-assisted extraction method was applied. The addition of cyclodextrin was found to increase the extraction efficiency of resveratrol (from 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 70 publications
(84 reference statements)
1
24
0
Order By: Relevance
“…The antioxidant properties of P. cuspidati extract have been widely described in literature data [ 8 ]. In the study mentioned above, we indicated that the extract was characterized by the best activity, where 1% m/w of β-cyclodextrin was added to the extraction mixture (ethanol: water (5:5 v:v )).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The antioxidant properties of P. cuspidati extract have been widely described in literature data [ 8 ]. In the study mentioned above, we indicated that the extract was characterized by the best activity, where 1% m/w of β-cyclodextrin was added to the extraction mixture (ethanol: water (5:5 v:v )).…”
Section: Resultsmentioning
confidence: 99%
“…The contents of main active compounds (polydatin, resveratrol, emodin and parietin) were determined by using the modified HPLC-Diode-Array Detection method described previously by Paczkowska-Walendowska et al [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous literature data on delivering polyphenols, especially resveratrol by this route is available. It has been proven that by the use of mucoadhesive polymers, a controlled and sustained release of resveratrol at the affected site can be achieved [169,170], which in combination with antioxidant and antibacterial properties can be a potential alternative in the treatment of periodontal diseases.…”
Section: Oromucosal Preparations and Formulations In Periodontitismentioning
confidence: 99%